ANALISIS KEBUTUHAN TENAGA PERAWAT BERDASARKAN PEDOMAN PERHITUNGAN DEPKES 2005 DI RUANG IRINA A TERATAI DI RSUP PROF. DR. R. D. KANDOU MANADO TAHUN 2021 - Ridwan Nurdin; Eva Mayadari; Cau Kim Jiu; Wida Kuswida Bhakti (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2022)
Abstract Background: The best service is part of the health service in the hospital, if the service improves the quality, the health service in the hospital will also be of good quality. The availability of human resources in quantity and quality is an important part of human resource planning. The purpose of this study was to analyze the need for nurses in the IRINA A Teratai Room. The method used in this study is a descriptive survey research that aims to describe the number of rational nurse needs based on the 2005 Ministry of Health guidelines. The results in this study based on an analysis of the needs of nurses guided by the Ministry of Health (2005) stated that nurses were still lacking in the IRINA room. A Teratai. According to the calculation that the need for nurses should return to 18, but currently only 14 nurses are available for HR planning in increasing the number of nurses according to the needs in the room which is very necessary because this will determine the quality and services provided. Keywords: Human Resources, Nurses, Manpower Needs